Implementación de la superconductividad en los estados de la materia para educación media - Anacona Beltrán, Judy Carolina; Acosta Urian, Yessica (Revista Científica, 2011)
What it wants to work in this proposal is the introduction of the superconductivity, as a matter state, in the middle school program (grades 10-11), in a practical, didactic and active way, from teacher to student and likewise inversely; through the application of pedagogical strategies that facilitate the understanding of it, promoting a scientific culture that allows a connection between physics and true life, that is not unknowledge to them; getting to a main goal of understand their multiple applications (MagLev Train) and the different action fields that it could have (superconductors in a ambient temperature). On the other hand it pretends to enable in the school the comprehension of the microscopically matter characteristic in the superconductivity state, because is necessary the approximation on this explanation for how is it; concluding with deeper ideas, than a relation of the flow facility of electric current in some materials in low temperatures and disappearance of the electric resistivity, taking into account that represented it represents the technological development more important of the twentieth century, for those and more reasons it is necessary to transmit this idea to each student.